PENERAPAN ALGORITMA SAPA PADA JARINGAN AD-HOC UNTUK MENGIDENTIFIKASI KOMPUTER BERBASIS MAC ADDRESS - Widyarto, Chris Tri; Wintolo, Hero; Indrianingsih, Yuliani (Compiler, 2013)
Wi-Fi waves are commonly used as an intermediary in the communication relationships in the wireless network. However, the use o f Wi-Fi waves can be used in addition to getting the relationship in the network, the user is also able to detect and identify other devices by using Wi-Fi waves. Ad-hoc network is a network that can be built independently by the computer with the Microsoft Windows operating system, to enable ad-hoc device has to have an identity that is SSID, the SSID is then activate the device can be detected by other devices. Activation is done ad-hoc by the netsh command is a shell command in the Windows 7 operating system. An ID must be unique for each device as there is no dual identity, to maximize the identification process. Utilizing MAC address as an identity is used, allowing the device to be uniquely identified. In addition to the MAC address is added to the device profile in the identity o f the device for easier identification. Sapa application users can identify the device is detected, and recognize it as a co-owned devices. Scheme which is the concept o f the algorithm Sapa. Sapa application allows device activation or notebook PC with the Windows 7 operating system to be detected and detected by other devices with the Windows 7 operating system and applications are also active Sapa. Communication is established indirect communication that occurs in a single direction. Detection range can be done up to 77 meters distance.